A study on the comparison population abundance of Oryctes rhinoceros in mature and immature on untreated oil palm / Wan Abdul Adziim Wan Azman - Wan Azman, Wan Abdul Adziim (Faculty of Plantation and Agrotechnology, 2019)
Rhinoceros beetles is one of the insect pest that attack oil palm and causing severe damage especially to immature oil palm. The infestation in high density of the beetles will reduce the oil palms‟ yield and economic loss to grower. A study in Melaka at share farm‟s UiTM Jasin and PPMSB was conducted to assess the population abundance of Oryctes rhinoceros in mature and immature oil palm using pheromone trap of ethyl-4-methylloctanoate. The data were collected weekly for about 3 months. The traps were applied using completely randomized design of experimental design with 4 replications for each plant age plot. Total beetles captured has been recorded to analyze their population in both stages. Each of the beetles has been identified their gender to evaluate their relationship with oil palms‟ age. Result shown that there was a significant difference (P< 0.05) in population of rhinoceros beetles in mature and immature oil palm. However there was no significant (P> 0.05) relationship between beetles‟ gender and oil palm age using Pearson‟s correlation. The study found that population of rhinoceros beetle in immature oil palm always exceed the population in mature oil palm. At the same time it was found that female Oryctes always dominated in all stages of oil palm. However, it was found that when female Oryctes in immature oil palm increase, the male in mature oil palm also increase. The infestation level in immature oil palm was higher compared to mature oil palm.